Valorization of Seaweed Wracks : Inclusion as Additive in Diets for Grass Carp (Ctenopharyngodon idella) - Galindo, Ana (2022)
Macroalgae have been recently described as a potential ingredient for aquafeeds, exerting several physiological benefits. Grass carp (Ctenopharyngodon idella) is a freshwater species, which has been the major fish species produced in the world in the last years. In order to determine the potential use of macroalgal wracks in fish feeding, C. idella juveniles were fed with an extruded commercial diet (CD) or the CD supplemented with 7% of a wind dried-powder (1 mm) from either a multispecific macroalgal wrack (CD + MU7) or a monospecific macroalgal wrack (CD + MO7) obtained from Gran Canaria island (Spain) coasts. After 100 days of feeding, survival, fish weight, and body indexes were determined, and muscle, liver, and digestive tract samples were collected. The total antioxidant capacity of macroalgal wracks was analyzed by assesing the antioxidant defense response and digestive enzymes activity in fish. Finally, muscle proximate composition, lipid classes (LC), and fatty acid (FA) profiles were also studied. Our results suggest that dietary inclusion of macroalgal wracks does not have negative effects on growth, proximate, and lipid composition, antioxidative status, or digestive capacity of C. idella. In fact, both macroalgal wracks caused a general lower fat deposition, and the multispecific wrack enhanced catalase activity in the liver.